2020
DOI: 10.1016/j.jcrc.2020.03.005
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on the efficacy and safety of chloroquine for the treatment of COVID-19

Abstract: a b s t r a c t a r t i c l e i n f o Available online xxxxPurpose: COVID-19 (coronavirus disease 2019) is a public health emergency of international concern. As of this time, there is no known effective pharmaceutical treatment, although it is much needed for patient contracting the severe form of the disease. The aim of this systematic review was to summarize the evidence regarding chloroquine for the treatment of COVID-19. Methods: PubMed, EMBASE, and three trial Registries were searched for studies on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
807
0
71

Year Published

2020
2020
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 991 publications
(910 citation statements)
references
References 10 publications
11
807
0
71
Order By: Relevance
“…org database dated March 21, 2020 showed 4 trials with chloroquine and 3 trials with HCQ which is currently under progress and have been summarized in Table 4. A list of 23 trials are already enlisted with both compounds at Chinese Clinical Trial Registry (http://www.chictr.org.cn) [41]. We believe that it would be wise to conduct a quick interim analysis from these trials as soon as possible to find out the results that can be applied to the masses across the globe to curb the menace of COVID-19 pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…org database dated March 21, 2020 showed 4 trials with chloroquine and 3 trials with HCQ which is currently under progress and have been summarized in Table 4. A list of 23 trials are already enlisted with both compounds at Chinese Clinical Trial Registry (http://www.chictr.org.cn) [41]. We believe that it would be wise to conduct a quick interim analysis from these trials as soon as possible to find out the results that can be applied to the masses across the globe to curb the menace of COVID-19 pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…During this early period, published research primarily explored the epidemiology [63], causes, clinical manifestation and diagnosis [64], as well as prevention and control of the novel coronavirus. Although these studies are relevant to control the current public emergency, more high-quality research is needed to provide valid and reliable ways to manage this kind of public health emergency in both the short-and long-term, including therapeutic options [65][66][67][68][69][70][71].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review included six articles and 23 ongoing clinical trials in China. CQ seems to be effective in limiting the replication of SARS-CoV-2 [90]. Gautret et al reported twenty cases were treated for 6 days with HCQ at the dosage of 600 mg/day plus azithromycin that showed a significant reduction of the viral carriage compared to controls.…”
Section: Chloroquine and Hydroxychloroquinementioning
confidence: 99%